A new evaluation methodology study - Integrating ‘ancient literature - clinical research - expert consensus’ firstly proposes eight elements for taking Chinese medicine decoctions - Li, Feiyu; Shang, Jing; Li, Yixuan; Liu, Guoxiu; Zhao, Sijin; Wu, Jiankun; Chen, Hongmei; Wu, Wanlin; Zhao, Xuelong; Zhai, Huaqiang (Frontiers in Pharmacology, 2025)
BackgroundThe scientific and rational use of Chinese medicine decoctions can improve their compliance, safety and efficacy. However, there is a lack of national-level best practice guidelines on the management of Chinese medicine decoctions, particularly in the rational use of them. We aim to establish a comprehensive and standardised reference standard comprising key elements of Chinese medicine decoctions.MethodsThis study was conducted using the method of “Ancient Literature - Clinical Research - Expert Consensus”. (1) Ancient literature analysis: Systematically analysed 1,019 records of Chinese medicine decoctions in “Bijiqi Qianjin Yaofang”, and initially extracted the elements related to the efficacy of the medicine. (2) Clinical research: A questionnaire covering the knowledge and demand of medication was designed and distributed to medical institutions in 12 regions, including Beijing and Shanghai, and 87 valid data were collected. The results showed that 69.62% of the practitioners had encountered difficulties in providing medication guidance, and 71.62% believed that standardised guidelines were urgently needed. Accordingly, a preliminary knowledge framework was formed. (3) Expert consensus: 20 Chinese and foreign clinical pharmacy experts (including France and U.S) were selected to prepare an advisory form based on the preliminary results, and a consensus was reached after two rounds of the Delphi method, confirming the content of the general and personalised guidance, covering terminology, usage, storage, contraindications and other dimensions, and finally identifying the eight core elements.ResultsThe method of “ancient literature-clinical research-expert consensus” is the first time to refine the eight elements of taking Chinese medicine decoctions. (1) Analysis of ancient literature reveals that temperature, course of treatment, frequency, dosage, time of administration, storage conditions, post-medication care and contraindications are the key influencing factors. (2) Clinical research confirmed the urgent need for standardised guidance, and a preliminary framework for a body of knowledge was constructed. (3) Standardised definitions of the eight elements were clarified through the Delphi Expert Consensus, including temperature, duration, frequency, dosage, time, storage conditions, post-medication care, and contraindications.ConclusionThis international guideline addresses a critical gap in taking Chinese medicine decoctions, offering an evidence-based framework for rational clinical use. Future efforts should prioritize expanded clinical validation and scenario-specific protocols to optimize standardization and safety.